2014
DOI: 10.1038/ajg.2014.74
|View full text |Cite
|
Sign up to set email alerts
|

Prucalopride Improves Bowel Function and Colonic Transit Time in Patients With Chronic Constipation: An Integrated Analysis

Abstract: Objectives:Constipation is often characterized by slow colonic transit, but the relationship between colonic transit time (CTT) and symptoms is unclear. The aims of this study were to investigate the effect of prucalopride, a 5-hydroxytryptamine receptor-4 agonist, on CTT and assess the relationship between CTT and symptoms.Methods:This was an integrated analysis of three randomized, placebo-controlled, phase 2 dose-finding trials of prucalopride in patients with chronic constipation (ClinicalTrials.gov identi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

7
46
1
3

Year Published

2016
2016
2024
2024

Publication Types

Select...
4
3
1

Relationship

1
7

Authors

Journals

citations
Cited by 68 publications
(57 citation statements)
references
References 31 publications
7
46
1
3
Order By: Relevance
“…However, there are several systematic reviews and meta-analyses evaluating the role of prucalopride [59][60][61][62][63][64][65][66][67][68] in the management of chronic constipation and their findings are consistent with the findings of the current study. Although the scope of the current article is the evaluation of clinical effectiveness and adverse events related to prucalopride only, previously reported systematic reviews [59][60][61][62][63][64][65][66][67][68] have reported its safety, efficacy, pharmacokinetics, and tolerability providing supporting evidence to our conclusions. As reported by Tack et al 69 "Prucalopride is an important addition to the therapeutic abilities for treating chronic constipation, especially in females poorly responding to laxatives.…”
Section: Discussionsupporting
confidence: 82%
See 2 more Smart Citations
“…However, there are several systematic reviews and meta-analyses evaluating the role of prucalopride [59][60][61][62][63][64][65][66][67][68] in the management of chronic constipation and their findings are consistent with the findings of the current study. Although the scope of the current article is the evaluation of clinical effectiveness and adverse events related to prucalopride only, previously reported systematic reviews [59][60][61][62][63][64][65][66][67][68] have reported its safety, efficacy, pharmacokinetics, and tolerability providing supporting evidence to our conclusions. As reported by Tack et al 69 "Prucalopride is an important addition to the therapeutic abilities for treating chronic constipation, especially in females poorly responding to laxatives.…”
Section: Discussionsupporting
confidence: 82%
“…45,46,54,57,63,65 Like other 5-HT 4 agonists such as cisapride, there were concerns about the risk of cardiac side effects after the use of prucalopride because prucalopride has not been found to interact with either the human ether-à-go-go-related gene (hERG) potassium channel (responsible for cisapride-induced arrhythmias) or 5-HT 1B receptors (mechanism behind tegaserod induced side effects), both assumed to be responsible for the bradycardia and cardiovascular adverse events. 45,46,51,56,57,59,63,69 In a similar study evaluating the cardiovascular safety profile of prucalopride in a relatively high-risk population of old-age care home patients with 80% having a prior history of cardiovascular disease, no significant hemodynamic or electrocardiographic changes were reported. Explicitly, there was no increased incidence of prolongation of the QT interval or bradycardia in the prucalopride group compared to placebo.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…15 A previous study in dogs demonstrated that prucalopride induces giant migrating contractions in the colon, 16 and it has been demonstrated to accelerate colonic transit both in healthy controls and in patients with chronic constipation, 14,17,18 possibly by mediating an increase in HAPCs, as was observed in healthy volunteers.…”
mentioning
confidence: 99%
“…4,16 The proportions of patients in the present study with at least three SCBMs per week (responders) were 44.2% ( Another study conducted by Emmanuel A et al, had shown responder rate of 42% at 4 weeks which is similar to our study. 18 Prucalopride had a good safety profile and was well tolerated in this study. Common adverse effects reported in our study were gastrointestinal disorders like diarrhea, nausea and abdominal pain and nervous system disorders like headache and dizziness.…”
Section: Discussionmentioning
confidence: 85%